The Us of Dice Game in Teaching Vocabulary for Young Learners - Humaira Humaira (Linguistics and ELT Journal, 2017)
Dice games is a cube (often with corners slightly rounded), Marked on each of its six faces with a different number of circular patches or Pits called pips. Based on the purpose of this research to find out whether the use of Loaded Dice Game can increase or not the students’ Vocabulary mastery at the fourth-grade students of SDIT Anak Sholeh Mataram in the school year 2016/2017. In this research, the writer used quasi-experimental research (pre-test and post-test design) with the population was 111 of 4 classes, and the sample was 58 students by using cluster sampling. The writer took two classes as samples, they are Malik class as an experimental and Khuzaifah class as a control group. To collect the data, the writer used multiple choices items with 20 numbers items. The finding of this research from the value of t-test was 5.01 higher than the value of t-table in the significance level 95% (1.67) and at the confidence level 99% (2.39). The value of t-test is higher than t-table, it means that the hypothesis alternative (Ha) is accepted. So, the writer can conclude that the use of Loaded Dice game can increase the students’ vocabulary mastery at the fourth-grade students of SDIT Anak Sholeh Mataram in the school year 2016/2017.